(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This study was performed to standardize the ultrasound estimated bladder weight as an additional non-invasive test for the measurement of the bladder outflow obstruction and to measure the therapeutic effects of bladder outflow obstruction in the follow-up after surgical correction of obstruction. This study was conducted from December 2012 to May 2014 where the sample size was 55 and sampling technique was purposive. In bladder outflow obstruction patient, transabdominal sonography was performed using a 7.5 MHz. probe. The anterior bladder wall thickness was measured in three points in the midline 1 cm apart and the average value was recorded. After that bladder volume was measured by ultrasonogram. In pre- and post-operative groups ultrasound estimated bladder weight was measured from bladder wall thickness and bladder volume. In this study, the mean ± SD of age was 48.8 ± 15.0 years. In bladder outflow obstruction patient, the pre-operative ultrasound estimated bladder weight was 117 ± 45.1 g which was reduced to 53.9 ± 10.8 g three months after surgical correction of obstruction. The ultrasound estimated bladder weight is a non-invasive, cheap and easily available additional diagnostic tool for detecting bladder outflow obstruction as well as it can measure the therapeutic effects in post-operative period.